2011
DOI: 10.1108/17515631111155124
|View full text |Cite
|
Sign up to set email alerts
|

NGO transformation: institutional entrepreneurship in Indian microfinance

Abstract: PurposeInstitutional theory is inspired by the problem of how different organizations operating in different environment have similar structures. The similarity is catalyzed by isomorphic forces, active within a given organizational field. Despite the force of isomorphic process, there is emergence of new organizations in through institutional entrepreneurs. The emergence of NBFCs through transformation of NGOs within the given context of Indian microfinance sector creates a space for examining the institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…detached from decision-making processes) are more likely to enact change because they are less embedded in the politics of institutionalised practices [25,95,189]. Only two of the reviewed studies, however, indicated that IEs were in a peripheral position and two studies did not state the social position of the IE [117,177,185,190]. In the remaining studies, all IEs held central, strategic roles within the NFP, including directors [118,187,188,191], senior managers [37,116,180,183,189],…”
Section: Priority Program Theoriesmentioning
confidence: 99%
See 4 more Smart Citations
“…detached from decision-making processes) are more likely to enact change because they are less embedded in the politics of institutionalised practices [25,95,189]. Only two of the reviewed studies, however, indicated that IEs were in a peripheral position and two studies did not state the social position of the IE [117,177,185,190]. In the remaining studies, all IEs held central, strategic roles within the NFP, including directors [118,187,188,191], senior managers [37,116,180,183,189],…”
Section: Priority Program Theoriesmentioning
confidence: 99%
“…The process of institutional work, however, was in response to the uncertainty (e.g. The second step is concerned with the rhetoric that IEs employ after they have identified an opportunity to try to "sell" their vision or idea [117,175,176,182]. Rather than simply bring attention to what is happening in the field and call for change, IEs seeking to build adaptive capacity create an environment conducive to the prospect of change.…”
Section: Priority Program Theoriesmentioning
confidence: 99%
See 3 more Smart Citations